2013
DOI: 10.1111/tpj.12147
|View full text |Cite
|
Sign up to set email alerts
|

Localization and evolution of septins in algae

Abstract: SUMMARYSeptins are a group of GTP-binding proteins that are multi-functional, with a well-known role in cytokinesis in animals and fungi. Although the functions of septins have been thoroughly studied in opisthokonts (fungi and animals), the function and evolution of plant/algal septins are not as well characterized. Here we describe septin localization and expression in the green algae Nannochloris bacillaris and Marvania geminata. The present data suggest that septins localize at the division site when cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…Finally, the role of the aspE septins, the presumed ancestral septins found in filamentous fungi and certain ciliates and algae, but missing from yeasts and animals (Pan et al, 2007; Nishihama et al, 2011; Yamazaki et al, 2013), may offer a clue to how filamentous fungi have maintained a diverse septin repertoire to condition morphogenetic plasticity. Perhaps AspE-type septins facilitate unique hetero-oligomeric associations during different developmental stages.…”
Section: How Do Septins Focus Invasive Growth By Fungi?mentioning
confidence: 99%
“…Finally, the role of the aspE septins, the presumed ancestral septins found in filamentous fungi and certain ciliates and algae, but missing from yeasts and animals (Pan et al, 2007; Nishihama et al, 2011; Yamazaki et al, 2013), may offer a clue to how filamentous fungi have maintained a diverse septin repertoire to condition morphogenetic plasticity. Perhaps AspE-type septins facilitate unique hetero-oligomeric associations during different developmental stages.…”
Section: How Do Septins Focus Invasive Growth By Fungi?mentioning
confidence: 99%
“…The number of septin genes varies widely between eukaryotic organisms, from 2 in nematodes to 13 in humans (25)(26)(27). Despite this variability, single particle electron microscopy and crystallography studies have shown that septins assemble into a conserved rodshaped heteromeric complex (also referred to as a protofilament) (Fig.…”
mentioning
confidence: 99%
“…Therefore, studies addressing the question of their assembly into possible homofilamentous assemblies, similar to those composed of multiple subunits, could be very informative. Thus far, only one report addresses this issue using a non-flagellate green alga (17). Their results show this unique septin to be localized within a ringlike structure in vivo and to be involved in cytokinesis.…”
mentioning
confidence: 96%
“…Their results show this unique septin to be localized within a ringlike structure in vivo and to be involved in cytokinesis. Furthermore, recombinantly expressed protein was capable of forming filamentous structures in vitro, implying that filaments composed of a single septin may play important physiological roles in some species (17).…”
mentioning
confidence: 99%